Bacterial assessment of phage magnetoelastic sensors for Salmonella enterica Typhimurium detection in chicken meat. (January 2017) - Chen, I-Hsuan; Horikawa, Shin; Bryant, Kayla; Riggs, Rebecca; Chin, Bryan A.; Barbaree, James M.
Abstract: Salmonella is one of the most common pathogens associated with foodborne illness in chickens. Food outbreaks from this pathogen haven't declined in the past 15 years according to the data from Centers for Disease Control and Prevention. It is our goal to improve food safety monitoring in this area by developing a real time Salmonella detection sensor on food surfaces. Previously, we demonstrated the use of phage C4-22 immobilized onto a rapid magnetoelastic (ME) biosensor for use as a front-line detection ligand to detect all Salmonella enterica serotypes in Tris Buffer Saline (TBS). In this study, by using fluorescent imaging, the phage peptide binding to Salmonella enterica serotype Typhimurium cells is again confirmed. Moreover, we constructed two detection models to evaluate the detection of Salmonella on/in chicken meat using the phage coated ME sensors. In the chicken surface detection method, phage C4-22 sensors demonstrated more than 12 times higher Salmonella binding capacity than the control sensors with no phage for the Salmonella spiked at the concentration of 7.86 × 10 5  cfu/mm 2 . In the second model, phage sensors were placed at different depths inside the chicken breast (0.1 cm; 0.5 cm; 1.0 cm below the meat surface) after surface inoculation of Salmonella . The second detection system showed that 23.27%–33% of the inoculated Salmonella cells absorbed inside the chicken breast fillets below 0.1 cm of the surface. The data for direct detection on chicken showed that phage C4-22 ME biosensors bind ultimately when there are high concentrations of Salmonella on the chicken surface. The results also suggest that the phage sensors can detect Salmonella effectively when the bacterial contaminants are absorbed into the chicken, and are not detectable by the surface detection method. Highlights: A novel, rapid, and sensitive phage ME biosensor method directly detects Salmonella on raw chicken. Proposed biosensor detection is simple and without sample preparation or pre-enrichment steps. A specific phage peptide probe was used for Salmonella detection on chicken samples. Biosensors enable for inside meat detection to monitor Salmonella contaminated absorbed into chicken.